The relevance of obesity for activities of daily living in geriatric rehabilitation patients - Wojzischke, Julia; Bauer, Jürgen M.; Hein, Andreas; Diekmann, Rebecca (Nutrients, 2021)
The obesity pandemic has reached old age but the effect of obesity on functional recovery in geriatric rehabilitation patients has not been investigated to date. In this prospective cohort study, patients admitted into geriatric rehabilitation were consecutively included between September 2015 and September 2016, aged ≥70 years. Individual activities of daily living were documented by the Barthel index (BI, 0-100 points). Obesity was assessed by the measurement of body mass index (BMI, kg/m²), waist circumference (WC, cm) and percentage of body fat mass (%FM) based on triceps’ skinfold thickness at admission (t1), discharge (t2) and six months after discharge (t3). A total of 122 patients were included in the analysis. Prevalence of obesity according to BMI, WC and %FM was 33.6%, 83.6% and 71.3% respectively. Patients with a high WC and patients with a high BMI had lower BI values at t1, t2, t3 and the improvement in BI (t1-t2, t2-t3) was lower than in those with low WC and low BMI, but without statistical significance. In multiple regression analysis, BMI, WC and %FM were not associated with BI at t3 and improvement of BI (t2-t3). Obesity was highly prevalent in geriatric rehabilitation patients, but it was not associated with BI during the 6-month follow-up.